Comparison of long-term prognosis for differentiated thyroid cancer according to the 7th and 8th editions of the AJCC/UICC TNM staging system. (May 2020) - Kim, Kwangsoon; Kim, Jin Kyong; Lee, Cho Rok; Kang, Sang-Wook; Lee, Jandee; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn
Background: The 8th edition of the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) tumor-node-metastasis (TNM) staging system was released with major revisions. The purpose of this retrospective study was to investigate differences between the 7th and 8th editions of the AJCC/UICC TNM staging system and to compare the predictability of prognosis between the two staging systems with patients who underwent thyroidectomy for differentiated thyroid cancer (DTC) at a single institution. Methods: A total of 3238 patients underwent thyroid operation from January 2002 to December 2006 at Yonsei University Hospital (Seoul, Korea), of which 2294 with complete clinical data and sustained follow up were enrolled. Clinicopathologic features and TNM staging by applying the 7th and 8th editions of the AJCC/UICC were analyzed retrospectively by the complete review of medical charts and pathology reports of patients. Mean follow-up duration was 132.9 ± 27.9 months. Results: A significant number of T3 patients were downstaged to T1 (838, 36.5%) and T2 (122, 5.3%). After applying the 8th edition of the AJCC/UICC TNM staging system, the number of stage I patients increased significantly from 1434 (62.5%) to 2058 (89.7%), whereas numbers of stage III and IV patients decreased significantly from 644 (28.1%) to 33 (1.4%) and from 199 (8.7%) to 17 (0.7%), respectively. According to Kaplan–Meier survival analyses and values of the Harrell's c-index and integrated area under the curve (iAUC), the 8th edition has significantly better predictive performance for disease-free survival (DFS) and disease-specific survival (DSS) than the 7th edition. Conclusions: A significant population was downstaged after applying the 8th edition of the AJCC/UICC TNM staging system, and the 8th edition provided significantly better accuracy in predicting DFS and DSS in patients with DTC.